Ultrasound Imaging of Cervical Anatomic Variants - Cordes, Michael; Coerper, Stephan; Kuwert, Torsten; Schmidkonz, Christian (Current Medical Imaging, 2021)
Embryologic developmental variants of the thyroid and parathyroid glands may cause cervical anomalies that are detectable in ultrasound examinations of the neck. For some of these developmental variants, molecular genetic factors have been identified. Ultrasound, as the first-line imaging procedure, has proven useful in detecting clinically relevant anatomic variants. The aim of this article was to systematically summarize the ultrasound characteristics of developmental variants of the thyroid and parathyroid glands as well as ectopic thymus and neck cysts. Quantitative measures were developed based on our findings and the respective literature. Developmental anomalies frequently manifest as cysts that can be detected by cervical ultrasound examinations. Median neck cysts are the most common congenital cervical cystic lesions, with a reported prevalence of 7% in the general population. Besides cystic malformations, developmental anomalies may appear as ectopic or dystopic tissue. Ectopic thyroid tissue is observed in the midline of the neck in most patients and has a prevalence of 1/100,000 to 1/300,000. Lingual thyroid accounts for 90% of cases of ectopic thyroid tissue. Zuckerkandl tubercles (ZTs) have been detected in 55% of all thyroid lobes. Prominent ZTs are frequently observed in thyroid lobes affected by autoimmune thyroiditis compared with normal lobes or nodular lobes (P = 0.006). The correct interpretation of the ultrasound characteristics of these variants is essential to establish the clinical diagnosis. In the preoperative assessment, the identification of these cervical anomalies via ultrasound examination is indispensable.
Keywords: thyroid anomalies